The Effect of Emotional Intelligence and Mental Health Towards Employee Performance Mediated by Job Satisfaction - Farrah Aulia Ramadhanty; Muafi Muafi (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2023)
This study aims to determine the effect of emotional intelligence and mental health on employee performance mediated by job satisfaction at Bank Rakyat Indonesia X Regency employees. This study used a quantitative research method by distributing questionnaires to 100 employees of Bank Rakyat Indonesia in X Regency. The sampling technique used in this study is saturated or census sampling. The final sample in the study amounted to 75 respondents. The analytical tool used in this study uses SmartPLS version 3.0 analysis with the structural equation modelling or SEM analysis method. The results of this study explain that; (1) there is no positive and significant effect of emotional intelligence on job satisfaction, (2) there is a positive and significant effect of mental health on job satisfaction, (3) there is a positive and significant effect of job satisfaction on employee performance, (4) there is no effect of satisfaction work mediates emotional intelligence on employee performance, and (5) there is an effect of job satisfaction mediating mental health on employee performance.